Reduce Waste using Integration of Lean Six Sigma and TRIZ Method: A Case Study in Wood Industry - Dian Hadi Purnomo; Muhammad Lukman (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
Recently, lean production has become a major focus of researchers and industry. The zero-waste concept holds an important role in the production process. The aim of this concept is to reduce waste and increase productivity. Wastes have significant negative impacts on the company, one of which is the decrease of company profit. This research aimed to integrate the Lean Six Sigma method with Teorya Resheniya Izobreatatelskikh Zadatch (TRIZ) in order to reduce wastes. These two methods were applied with Define-Measure-Analyze-Improve-Control(DMAIC) methodology. A case study was conducted in a wood manufacturing company. The results of the study suggest that the application of the two methods can significantly reduce the Non-value Added (NVA).